(Eyewitness books) Pirate - Platt, Richard; Chambers, Tina (Dorling Kindersley London, 2000)
Here is a spectacular and informative guide to the dangerous and adventurous life of piracy, privateering, and buccaneering. Full-color photographs of weapons, ships, flags, maps, and treasure offer a unique and revealing view of pirate life on the high seas